PENGARUH MOTIVASI, LINGKUNGAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL TRUNTUM PADANG - Putri, Fani Melda; Sophian, Sophan (Ensiklopedia of Journal, 2024)
Employee performance is the most systematic assessment to determine the results of employee work. If the employee's work value must be greater than the work performance that is considered, the agency gets a positive value from the employee's work program. This study aims to determine the influence of motivation, work environment, and work discipline on the performance of Truntum Padang Hotel employees. The type of research used is quantitative, the object of research is employees of Truntum Padang Hotel. The population in this study was all employees at Truntum Padang Hotel, which was 148 samples using total sampling techniques. Research measuring instruments using Likert scale questionnaires and data analysis using multiple linear regression tests. Data processing using IBM's SPSS program version 25.  The results showed that motivation, work environment, and work discipline had a positive and significant influence on the performance of Truntum Padang Hotel employees. Keywords: motivation, work environment, discipline, employee performance.